Hedge funds and financial stability: Regulating prime brokers will mitigate systemic risks - King, Michael R.; Maier, Philipp (Journal of Financial Stability, 2009)
We review key characteristics of the hedge fund industry, and identify conditions under which this sector can pose a threat to financial stability. Direct regulation of hedge funds that increases transparency does not appear feasible, may create a moral-hazard problem, and may reduce market liquidity. Indirect regulation by prime brokers and market discipline by creditors, counterparties, and investors have been effective in limiting the risks from the hedge fund sector. To reduce systemic risks, more regulation of prime brokers is warranted to avoid competitive dynamics from undermining counterparty risk management practices.